2012
DOI: 10.1177/0959683612449755
|View full text |Cite
|
Sign up to set email alerts
|

Late-Holocene marine radiocarbon reservoir correction (ΔR) for the west coast of South Africa

Abstract: In order to calibrate radiocarbon ages based on samples with a marine carbon component it is important to know the marine carbon reservoir correction or ΔR value. This study measured the ΔR on both known-age pre-bomb marine shells and paired marine and terrestrial samples from two regions on the west coast of South Africa: the southwestern Cape and Namaqualand. Pooling the data by region produces ΔR values that are similar enough to use a west coast weighted mean ΔR of 146 ± 85 14C years to correctly calibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…This paper reports that the south coast has higher ∆R values than the east coast, and supplements those of Dewar et al (2012) for the west coast. Further studies on the hydrography of the south and east coasts may help to cast further light on this finding, and increase both the volume and quality of reservoir correction data for the region.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…This paper reports that the south coast has higher ∆R values than the east coast, and supplements those of Dewar et al (2012) for the west coast. Further studies on the hydrography of the south and east coasts may help to cast further light on this finding, and increase both the volume and quality of reservoir correction data for the region.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, according to the results outlined, ∆R values from the south and east coastal regions represent statistically significant sub-sets when evaluated with a t-test. Prior to this study, only three ∆R studies have been reported across the entire coastline of South Africa (Southon et al, 2002;Dewar et al, 2012; (Table 4), with the study by Dewar et al (2002) confined to the west coast. The ∆R value determined for the east coast by Southon et al (2002) was based on a marine shell collected in Kwa-Zulu Natal that yielded a ∆R value of 213 ± 57 (recalculated with MARINE13) (Sample R) which accords within the uncertainty with the ∆R values presented here for this eastern part of the South African coast.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations